2018
DOI: 10.1186/s12886-018-0987-8
|View full text |Cite
|
Sign up to set email alerts
|

UVB-mediated down-regulation of proteasome in cultured human primary pterygium fibroblasts

Abstract: BackgroundPterygium is a condition characterized by epithelial overgrowth of the cornea, inflammatory cell infiltration and an abnormal extracellular matrix accumulation. Chronic UV exposure is considered as a pathogenic factor of this disease. Proteasome is an intracellular multi-subunit protease complex that degrades intracellular proteins. Among proteasome subunits the β5 (PSMB5), bearing chymotrypsin-like activity. It is considered as the main proteasome subunit and its expression is mediated by Nrf2-ARE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Pterygium is postulated to occur due to localized dysfunction of nasal limbal stem cells consequential to exposure to UVB light. [ 18 ] This theory forms the basis of the incorporation of limbal stem cells in the surgical treatment of pterygium. Of all the techniques described in literature, [ 3 , 4 ][ 5 ][ 6 ] CAG modality has been found to be associated with the lowest recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Pterygium is postulated to occur due to localized dysfunction of nasal limbal stem cells consequential to exposure to UVB light. [ 18 ] This theory forms the basis of the incorporation of limbal stem cells in the surgical treatment of pterygium. Of all the techniques described in literature, [ 3 , 4 ][ 5 ][ 6 ] CAG modality has been found to be associated with the lowest recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that UV exposure is a factor precipitating the development of pterygium (3,21,32,33). Histological examination has confirmed that elastic connective tissue lesions and severely damaged areas of the Bowman membrane indicate direct damage caused by solar radiation or indirect damage due to excessive proteolytic activity (3,21).…”
Section: Discussionmentioning
confidence: 99%
“…Pterygium occurs primarily due to local de ciency of limbal stem cells(LSCD)secondary to exposure to UV type B(UVB) light 18 . The basic difference between the primary and recurrent pterygium is that the body of the former is free from the underlying structures whereas that of the latter is rmly adherent to the underlying tissues namely episclera and sclera.This is primarily the reason one has to be extremely careful and diligent in the surgical treatment of pterygium to avoid complications and nancial implications .…”
Section: Discussionmentioning
confidence: 99%